Infectious diseases and autoimmunity - Lucia Gemma Delogu; Silvia Deidda; Giuseppe Delitala; Roberto Manetti (Journal of Infection in Developing Countries)
Introduction: Autoimmunity occurs when the immune system recognizes and attacks host tissue. In addition to genetic factors, environmental triggers (in particular viruses, bacteria and other infectious pathogens) are thought to play a major role in the development of autoimmune diseases.